Penyuluhan Gizi Seimbang pada Remaja di SMAS PGRI Ge’tengan, Kabupaten Tana Toraja - Hayuti Windha Pagiu; Suharnita Wijaya; Fera Dwiyanti; Nofita Tudang Rombeallo (Lembaga Pengembangan Kinerja Dosen, 2024)
Adolescence is very important to pay attention to because it is a transition period between children and adults, where physically they will experience specific changes. Adolescents must receive balanced nutritional intake according to their needs in order to achieve optimal growth and development and avoid nutritional problems. Nutritional problems that can occur in adolescents are malnutrition, chronic lack of energy (KEK), obesity and anemia (Sandra, Ahmad, & Arinda, 2017). An imbalance between the intake of food consumed causes problems of undernutrition and overnutrition. Malnutrition in adolescents results in decreased body resistance to disease, increased disease rates, abnormal growth, low intelligence levels, low productivity and stunted growth of reproductive organs in adolescents (Nurfiriani & Ratih, 2023). The aim of this service activity is to increase teenagers' knowledge about the importance of nutrition for teenagers, to support the growth and development of teenagers, to prevent the risk of nutritional problems and non-communicable diseases, so it is necessary to carry out health promotion efforts in the form of providing health education and evaluations to increase knowledge about nutrition so that it can increase adolescent awareness in maintaining health.